2021
DOI: 10.1002/mrd.23522
|View full text |Cite
|
Sign up to set email alerts
|

Proteome profiling of chicken ovarian follicles immediately before and after cyclic recruitment

Abstract: A shotgun proteomics study using isobaric tags for relative and absolute quantification labeling was conducted to characterize proteins in chicken ovarian follicles immediately before and after cyclic recruitment. Granulosa cell (GC) layers from the most recently recruited follicle (GC9) and from each of the four largest prerecruitment follicles (GC1-4) plus theca tissue (TH) from the most recently recruited (TH9) and largest prerecruitment (TH1) follicles were compared. Of 1535 proteins identified, none were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…RLN3 is significantly enriched in this pathway and is highly expressed during the peak egg-laying period. Relaxin-like peptides, such as RLN3 , are produced in granulosa cells post-ovulation and play a role in promoting egg laying, impacting the oviduct and ovary ( Ghanem and Johnson, 2021 ). Additionally, in the protein-protein interaction network, we observed an interaction between RLN3 and SCG2 ( Figure 6B ).…”
Section: Discussionmentioning
confidence: 99%
“…RLN3 is significantly enriched in this pathway and is highly expressed during the peak egg-laying period. Relaxin-like peptides, such as RLN3 , are produced in granulosa cells post-ovulation and play a role in promoting egg laying, impacting the oviduct and ovary ( Ghanem and Johnson, 2021 ). Additionally, in the protein-protein interaction network, we observed an interaction between RLN3 and SCG2 ( Figure 6B ).…”
Section: Discussionmentioning
confidence: 99%
“…In another transcriptome analysis between the two divergent chicken breeds, which are in the laying phase and the brooding phase, the expression of RLN3 mRNA shows downregulation in brooding chickens, thus pointing out its role actively involved in reproductive biology ( Shen et al, 2016 ). The report that RLN3 is actively involved in female reproductive biology also comes from the study by Ghanem and Johnson (2021 ) in a shotgun proteomics study using isobaric tags to characterize the proteins in chicken ovarian follicles immediately before and after cyclic recruitment. RLN3 is revealed to be distinctively expressed in a total of 1,535 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we indicated that eIF2 signaling and the regulation of eIF4 and p70S6K signaling pathways-both involved in protein synthesisare the most significant canonical pathways in the transcriptome, as well as in the proteome, of mature egg coats. The eIF2 signaling pathway has recently been identified in chicken follicles after cyclic recruitment, and eIF2 activation reflects the demand for enhanced protein synthesis during follicle development [28]. In bird oogenesis, primary follicles aprox.…”
Section: Protein Synthesismentioning
confidence: 99%
“…Interestingly, we also observed the presence of a membrane estrogen receptor, GPER1, which, together with ESRs, may be involved in estrogen signaling in mature egg coats. In birds, GPER signaling has been described in the GCs of chicken ovarian follicles before and after cyclic recruitment [28], and its role in GC differentiation and promoting follicle survival has been reported [71]. Estrogen binding to GPER activates a stimulatory G protein, resulting in the stimulation of adenylyl cyclase activity and cAMP levels, which are involved in maintaining the estrogen-induced meiotic arrest of oocytes before fertilization in vertebrates [72].…”
Section: Estrogen Receptor Signalingmentioning
confidence: 99%
See 1 more Smart Citation